The Relationship Between Reading Strategy and Reading Comprehension: A Meta-Analysis - Sun, Yuanke; Wang, Jindao; Dong, Yang; Zheng, Haoyuan; Yang, Jie; Zhao, Yaman; Dong, Weiyang (Frontiers in Psychology, 2021)
This study synthesized the correlation between reading strategy and reading comprehension of four categories based on Weinstein and Mayer's reading strategy model. The current meta-analysis obtained 57 effect sizes that represented 21,548 readers, and all selected materials came from empirical studies published from 1998 to 2019. Results showed that reading strategies in all the four categories had a similar correlation effect size with reading comprehension. The correlation between monitoring strategy and reading comprehension was significantly larger in first language scripts than second language scripts. Affective strategy and elaboration strategy had an independent effect on reading comprehension, which was not significantly moderated by selected moderators. Results suggested that the reading strategies of all the four categories may have a similar contribution to text comprehension activities.